Investor Relations

polignac endversion.pdf

Description
In this paper, we will rst establish that there are many primes p such that p+n is prime for an even integer n , by using the Chébotarev-Artin's theorem, the inclusion-exclusion principle of Moivre, Mertens formula. With these tools we get a
Published
of 7
All materials on our website are shared by users. If you have any questions about copyright issues, please report us to resolve them. We are always happy to assist you.
Related Documents
Share
Transcript
          ( ISE   2)              p    p + n       p    p  +  n    X   +  n   √  X   +  n    X    m  = inf  { n  ∈  2 N ∗  :  p  +  n  ∈  P }           n    n    n    p    p  +  n      p  +  n    n     X   ∈  R    n    [ √  X,X  ]    α n ( X  ) − α n ( √  X  )  ≥  2 c 2 ( X  )Π( X   +  n )ln X  √  X    p =3 ,p | n  p − 1  p − 2  − Π( n  + 1)   C  X   =  { 9 , 15 , 21 , 25 , 27 , 33 ...... }    [9 ,X  ]    3  p    2  p    p    √  X     P  √  X       p ∈P  √  X ( A 2  p  +  n )   A 2  p  +  n  =  A 2  p + n  =  { 3  p  +  n, 5  p  +  n, 7  p  +  n,....... (1 + 2  p  X   −  p 2  p   )  p  +  n }   3  p + n    2  p     p     n           X >  0    n    C  X     [9 ,X  ]    f  n  :  C  X   →  C  X   +  nc  →  c  +  n   IC  ≤ X  + n    C  X   +  n    G ≤ X  + n    P  ≤ X  + n    p    p  ≤  X  + n   δ  n ( X  ) =  card ( G ≤ X  + n )    α n ( X  ) =  card (  p  ∈ P  ≤ X  + n \ G ≤ X  + n  :  p  ≥  n  + 1)   Π( X   +  n ) =  card ( P  ≤ X  + n )    Π( X   +  n ) =  δ  n ( X  ) +  α n ( X  ) + Π( n  + 1)   c  ∈  C  X     p  ≤√  X     P  ≤√  X   =  {  p 1 ,p 2 ,....,p r }    p 1  = 2    p 2  = 3    p r  = max( P  ≤√  X  )    C  X   =   p ∈P  ≤√  X ,p ≥ 3 A 2  p   C  X   +  n  =   p ∈P  ≤√  X ,p ≥ 3 A 2  p + n   ∀ n    ∀  p  ∈ P  ≤ X  + n \ G ≤ X  + n    p > n  + 1    p − n  ∈ P  ≤ X    ∀ n    ∀  p  ∈ P  ≤ X  + n \ G ≤ X  + n    p > n  + 1    p − n  ∈  [1 ,X  ] \ C  X     p − n    p − n <  9    p − n  ≥  9     p − n / ∈  C  X     lim X  → + ∞ α n ( X  ) = + ∞         p ∈P  ≤√  X ,p ≥ 3  A 2  p + n       a,b >  0    gcd( a,b ) = 1    Π( X,a,b ) =  card (  p  ≤  X,p  ≡  a [ b ])    ∃ c >  0    Π( X,a,b ) =  L i ( X  ) φ ( b )  +  ( cXe −√  ln X  )   Π( X  ) =  L i ( X  ) +  X  ln 2 ( X  )   Π( X,a,b ) =  Π( X  ) φ ( b )  +  ( cXe −√  ln X  )       a,b >  0    gcd( a,b ) = 1    Π( X,a,b ) =  card (  p  ≤  X,p  ≡  a [ b ])    ∃ c >  0    Π( X,a,b )Π( X  ) = 1 φ ( b ) +  ( c ln Xe −√  ln X  )          gcd( a,b ) = 1   1 φ ( b )  +  ( c ln Xe −√  ln X  )     k j =1 ,p ij ∈P  ≤√  X A 2  p ij + n   1  ≤  i 1  < i 2  < ..... < i k     k >  2     k j =2 ,p ij ∈P  ≤√  X A 2  p ij    k j =2  p i j   k   j =2 ,p ij ∈P  ≤√  X A 2  p ij + n  =  { (2 m  + 1) k   j =2  p i j  +  n | 0  ≤  m  ≤  X   −  k j =2  p i j 2  k j =2  p i j }   2  k j =2  p i j    k j =2  p i j  +  n    gcd(2  k j =2  p i j ,  k j =2  p i j  +  n ) = 1     k j =2  p i j     n         X >  0    c 2    α n ( X  )    p  ≤  X     p  +  n    ∃   β  n ( X  ) =  c 2 ( X  )2  √  X  p =3 ,p | n p − 1  p − 2    X  0    ∀ X   ≥  X  0 α n ( X  ) − α n ( √  X  )  ≥  β  n ( X  )Π( X   +  n )ln X   − Π( n  + 1)     a 1 ,a 2 ,......a r   1 − r  i =1 1 a i +  1 ≤ i<j ≤ r 1 a i a  j +  .....  + ( − 1) r a 1 a 2 ....a r = r  i =1 a i − 1 a i     P  ( X  ) =  ri =1 ( X   −  1 a i )   P  ( X  ) =  X  r + r  k =1  1 ≤ i 1 <i 2 <....<i k ≤ r ( − 1) k X  r − k  k j =1  a i j   X   = 1            (   p ∈P  ≤√  X ,p ≥ 3 ,p    n A 2  p + n ) = r  k =2 ( − 1) k  2 ≤ i 2 <i 3 <....<i k ≤ r  ( k   j =2 ,p ij ∈P  ≤√  X ,p ij    n A 2  p ij + n )       ( C  X   +  n ) =   (   p ∈P  ≤√  X ,p ≥ 3 ,p    n A 2  p + n ) =  δ  n ( X  )Π( X   +  n )   ∀ k  ≥  3  ( k   j =2 ,p ij ∈P  ≤√  X ,p ij    n A 2  p ij + n ) = 1 φ (2  k j =2  p i j )+  h ( X   +  n ) ∀ i ≥  2  ( A 2  p i + n,p i    n ) = 1 φ (2  p i )  −  ψ  p i + n Π( X   +  n ) +  h ( X   +  n )   ψ  p i + n  = 1 , 0    p i  +  n    h ( X   +  n ) =   ( c ln( X   +  n ) e − √  ln( X  + n ) )   δ  n ( X  )Π( X   +  n ) =  g ( X   +  n ) − r  k =2 ψ  p k + n Π( X   +  n ) + r  k =2  2 ≤ i 2 <i 3 <...<i k ≤ r ( − 1) k  k j =2 (  p i j  − 1) ,p i j     n   | g ( X   +  n ) h ( X   +  n ) |  =  | r  k =2 ( − 1) k  2 ≤ i 2 <i 3 <....<i k ≤ r 1 |  =  | r  k =2 ( − 1) k  r − 1 k − 1  |  =  |− r − 1  k =1 ( − 1) k  r − 1 k  |  = 1    rk =2  ψ  p k + n  =  α n (  p r )   δ  n ( X  )Π( X   +  n ) =  h ( X   +  n ) −  α n (  p r )Π( X   +  n ) + (1 − r  i =2 ,p i    n  p i − 2  p i − 1)   δ  n ( X  ) = Π( X   +  n ) − α n ( X  ) − Π( n  + 1)    r  = max( i |  p i  ≤√  X  )   α n ( X  ) − α n ( √  X  )  ∼ + ∞  Π( X   +  n ) √  X    p =3 ,p    n  p − 2  p − 1  − Π( n  + 1)   c n ( X  ) =  √  X  p =3 ,p    n p − 2  p − 1    √  X    p =3  p − 2  p − 1 = √  X    p =3 ,p    n  p − 2  p − 1 √  X    p =3 ,p | n  p − 2  p − 1   c n ( X  ) = √  X    p =3 ,p | n  p − 2  p − 1 √  X    p =3  p − 1  p − 2          p ≤ X  (1 −  1  p ) =  e − γ  ln X  (1 +  ( 1ln X  ))     p ≤√  X  (1 −  1  p ) = 2 e − γ  ln X   (1 +  ( 1ln X  ))   c 2 ( X  ) = √  X    p =3  p (  p − 2)(  p − 1) 2  = √  X    p =3  p p − 1 √  X    p =3  p − 2  p − 1   c n ( X  ) = 2 c 2 ( X  ) √  X    p =2 (1 −  1  p ) √  X    p =3 ,p | n  p − 1  p − 2   c n ( X  ) = 4 c 2 ( X  ) e − γ  ln X   (1 +  ( 1ln X  )) √  X    p =3 ,p | n  p − 1  p − 2 α n ( X  ) − α n ( √  X  )  ∼ + ∞  Π( X   +  n )[4 c 2 ( X  ) e − γ  ln X  √  X    p =3 ,p | n  p − 1  p − 2] − Π( n  + 1) ∃ X  0  ∀ X   ≥  X  0 α n ( X  ) − α n ( √  X  )  ≥  2 c 2 ( X  )Π( X   +  n )ln X  √  X    p =3 ,p | n  p − 1  p − 2  − Π( n  + 1)      ∀ X   ≥  2 , ∀ n  ≥  1    ln(Π( X   + 2 n ))  <  ln( X   + 2 n )  <  2ln(Π( X   + 2 n ))     ∀ X >  0 Π( X   + 2 n )  < X   + 2 n   ∀ X >  2   √  X   + 2 n >  ln( X   + 2 n )    [Π( X   + 2 n )] 2   ( X  +2 n ) 2 (ln( X  +2 n )) 2       X     n   ∀ X >  5000 ,n 2  X,α n ( X  )  >  16 β  n ( X  )Π(Π( X   +  n )9ln X   
We Need Your Support
Thank you for visiting our website and your interest in our free products and services. We are nonprofit website to share and download documents. To the running of this website, we need your help to support us.

Thanks to everyone for your continued support.

No, Thanks